Case reportsSuccessful angioplasty for radial artery chronic total occlusion in a patient with digital gangrene - Tasal, Abdurrahman; Bacaksiz, Ahmet; Erdogan, Ercan; Goktekin, Omer (Advances in Interventional Cardiology/Postępy w Kardiologii Interwencyjnej, 2013)
Critical hand ischemia caused by chronic occlusive arterial disease is an uncommon condition. Diabetes mellitus and chronic renal insufficiency are the concomitant conditions in most of these patients. A 59-year-old woman with diabetic nephropathy being treated with hemodialysis was referred to the Cardiology Department for a non-healing necrotic lesion in the distal part of the fourth finger. We performed balloon angioplasty for diffuse and severe calcified total occlusion of the radial artery using long and high pressure resistant balloons. After successful angioplasty the symptoms were relieved immediately and the finger was almost healed within 2 months of follow-up.